Decoding interaction between mitochondria and endoplasmic reticulum in ischemic myocardial injury: targeting natural medicines - Zhang, Chuxin; Chang, Xing; Zhao, Dandan; He, Yu; Dong, Guangtong; Gao, Lin (Frontiers in Pharmacology, 2025)
Ischemic cardiomyopathy (ICM) is a special type or end stage of coronary heart disease or other irreversible ischemic myocardial injury. Inflammatory damage to coronary vessels is a crucial factor in causing stenosis or occlusion of coronary arteries, resulting in myocardial ischemia and hypoxia, but it is also an aspect of cardioprotection that is often overlooked. This review discusses the mechanisms of vascular injury during ICM, in which inflammation and oxidative stress interact and trigger cell death as the cause of coronary microvascular injury. Imbalances in endoplasmic reticulum function and mitochondrial quality control are important potential drivers of inflammation and oxidative stress. In addition, many studies have confirmed the therapeutic effects of Chinese herbal medicines and their natural monomeric components on vascular injuries. Their mitochondrial quality control and endoplasmic reticulum protection mechanisms as well as their role in combating improvements in vascular endothelial function and attenuating vascular injury are also summarized, with a perspective to provide a reference for pathologic understanding, drug research, and clinical application of ICM-associated coronary microvascular injury.